Integrating orange combating vitamin A deficiency in maize-based food systems in Zambia - International Potato Center (2012)
In year 1, three pro-vitamin A rich orange-fleshed sweetpotatoes (OFSP) bred by the national program have been selected based on-farm trials for further testing, multiplication and demonstration. Farmers are being identified and trained as quality vine multipliers and hosts of demonstration plots for the next season.